Childhood interstitial lung disease in Turkey: first data from the national registry - GÖKDEMİR, YASEMİN; KARADAĞ, BÜLENT TANER (My University, 2023)
Abstract: The childhood interstitial lung diseases (chILD) Turkey registry (chILD-TR) was established in November 2021 to increase awareness of disease, and in collaboration with the centers to improve the diagnostic and treatment standards. Here, the first results of the chILD registry system were presented. In this prospective cohort study, data were collected using a data‐entry software system. The demographic characteristics, clinical, laboratory, radiologic findings, diagnoses, and treatment characteristics of the patients were evaluated. Clinical characteristics were compared between two main chILD groups ((A) diffuse parenchymal lung diseases (DPLD) disorders manifesting primarily in infancy [group1] and (B) DPLD disorders occurring at all ages [group 2]). There were 416 patients registered from 19 centers. Forty-six patients were excluded due to missing information. The median age of diagnosis of the patients was 6.05 (1.3–11.6) years. Across the study population (n = 370), 81 (21.8%) were in group 1, and 289 (78.1%) were in group 2. The median weight z-score was significantly lower in group 1 (− 2.0 [− 3.36 to − 0.81]) than in group 2 (− 0.80 [− 1.7 to 0.20]) (p < 0.001). When we compared the groups according to chest CT findings, ground-glass opacities were significantly more common in group 1, and nodular opacities, bronchiectasis, mosaic perfusion, and mediastinal lymphadenopathy were significantly more common in group 2. Out of the overall study population, 67.8% were undergoing some form of treatment. The use of oral steroids was significantly higher in group 2 than in group 1 (40.6% vs. 23.3%, respectively; p = 0.040). Conclusion: This study showed that national registry allowed to obtain information about the frequency, types, and treatment methods of chILD in Turkey and helped to see the difficulties in the diagnosis and management of these patients. What is Known: • Childhood interstitial lung diseases comprise many diverse entities which are challenging to diagnose and manage. What is New: • This study showed that national registry allowed to obtain information about the frequency, types and treatment methods of chILD in Turkey and helped to see the difficulties in the diagnosis and management of these patients. Also, our findings reveal that nutrition should be considered in all patients with chILD, especially in A-DPLD disorders manifesting primarily in infancy.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Health Sciences; Klinik Tıp (MED); Klinik Tıp; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; PEDIATRICS; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics, Perinatology and Child Health; Childhood; Interstitial lung disease; Registry